1991
DOI: 10.1210/endo-129-3-1402
|View full text |Cite
|
Sign up to set email alerts
|

Functional Antagonism between Endogenous Mouse Growth Hormone (GH) and a GH Analog Results in Dwarf Transgenic Mice*

Abstract: A dwarf transgenic mouse (DTM) line has been established in which mice express relatively high levels of a mutated bovine (b) GH gene. This bGH analog binds to mouse liver membrane preparations with an affinity similar to that of wild-type bGH. The mean growth ratio of these mice is approximately 0.7 relative to that of their nontransgenic littermates. Serum insulin-like growth factor-I (IGF-I) levels of DTM were found to be approximately half those in nontransgenic littermates. Liver GH receptor levels were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
136
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(148 citation statements)
references
References 38 publications
11
136
1
Order By: Relevance
“…Taking together these observations we can suggest that local manipulation of JAK-STAT activation can be a very perspective therapeutic approach for managing of cholangiocarcinoma at different stages of its progression. Recent advances in development of hormonal and cytokine antagonists (recombinant proteins for Prl and GH and peptide for IL-6 [145][146][147] ) give us an efficient tool for this treatment. Since synthetic specific inhibitors of JAK and other tyrosine kinases are intensively developed, we could suggest their efficient application for managing of cholangiocarinoma in addition to antagonists.…”
Section: Perspective Therapeutic Addressing Of the Jak-stat Pathwaymentioning
confidence: 99%
“…Taking together these observations we can suggest that local manipulation of JAK-STAT activation can be a very perspective therapeutic approach for managing of cholangiocarcinoma at different stages of its progression. Recent advances in development of hormonal and cytokine antagonists (recombinant proteins for Prl and GH and peptide for IL-6 [145][146][147] ) give us an efficient tool for this treatment. Since synthetic specific inhibitors of JAK and other tyrosine kinases are intensively developed, we could suggest their efficient application for managing of cholangiocarinoma in addition to antagonists.…”
Section: Perspective Therapeutic Addressing Of the Jak-stat Pathwaymentioning
confidence: 99%
“…A series of highly specific antagonists of the GH action has recently been developed for the potential therapeutic use in various pathophysiological conditions, including diabetes. Initially it was shown that alteration of single amino acids in the third a-helix of bovine (b)GH (residues 109±126) results in a GH antagonist [68,69]. In vitro experiments showed that this new group of GH antagonists binds to the GH receptor with the same affinity as native GH but in vivo a phenotypic dwarf animal characterized by low circulating IGF-I concentrations and a proportional body composition develops when the GH antagonist is expressed in transgenic (TG) mice [68,69].…”
Section: Agents With Effects On the Altered Gh/igf Axis In Diabetic Kmentioning
confidence: 99%
“…Initially it was shown that alteration of single amino acids in the third a-helix of bovine (b)GH (residues 109±126) results in a GH antagonist [68,69]. In vitro experiments showed that this new group of GH antagonists binds to the GH receptor with the same affinity as native GH but in vivo a phenotypic dwarf animal characterized by low circulating IGF-I concentrations and a proportional body composition develops when the GH antagonist is expressed in transgenic (TG) mice [68,69]. Studies in long-term diabetic GH antagonist TG mice, that express the GH antagonist (bGH-G119R or hGH-G120R), have shown that these animals are protected against development of diabetic renal changes [70,71].…”
Section: Agents With Effects On the Altered Gh/igf Axis In Diabetic Kmentioning
confidence: 99%
“…The transgene is a mutated bGH gene in which the codon for glycine at position 119 is replace by arginine or lysine (G119K) [51][52][53]. Expression of these two mutated GH transgenes surprisingly results in reduced GH action and was later found to be a classic receptor antagonist [54].…”
Section: Gha Transgenic Micementioning
confidence: 99%